2021
DOI: 10.3389/fphys.2021.645212
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Crucial Mediators for Carotid Atherosclerosis Pathogenesis Through Integration of Microbiome, Metabolome, and Transcriptome

Abstract: BackgroundCarotid atherosclerosis (CAS) is an important cause of stroke. Although interactions between the gut microbiome and metabolome have been widely investigated with respect to the pathogenesis of cardiovascular diseases, information regarding CAS remains limited.Materials and MethodsWe utilized 16S ribosomal DNA sequencing and untargeted metabolomics to investigate the alterations in the gut microbiota and plasma metabolites of 32 CAS patients and 32 healthy controls. The compositions of the gut microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…More importantly, without homeostatic control urine have the potential to detect the small and early pathological changes (Wu and Gao, 2015;Wu et al, 2021). Mass spectrum-based omics methods have been used in the biomarker discovery of CAS, and the sample source mainly contained blood or atherosclerosis plaque (Vorkas et al, 2016;Li et al, 2017;Lee et al, 2019;Ji et al, 2021). Until now, there is still no available urinary biomarker for CAS.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, without homeostatic control urine have the potential to detect the small and early pathological changes (Wu and Gao, 2015;Wu et al, 2021). Mass spectrum-based omics methods have been used in the biomarker discovery of CAS, and the sample source mainly contained blood or atherosclerosis plaque (Vorkas et al, 2016;Li et al, 2017;Lee et al, 2019;Ji et al, 2021). Until now, there is still no available urinary biomarker for CAS.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the differences in plasma metabolites between AAA and AS, 32 AAA and 32 AS patients were included in this study. The clinical characteristics of these participants are shown in Table 1 (Ji et al, 2021). Patients with AAA were slightly older (P=0.019), but there were no differences in gender, body mass index (BMI), or underlying diseases such as hypertension and diabetes, which would affect metabolism.…”
Section: Clinical Characteristics Of Aaa and As Patientsmentioning
confidence: 99%
“…In recent years, several studies have confirmed the presence of bacterial DNA in atherosclerotic plaque which may contribute to the development of cardiovascular disease (52). In addition, researchers have also found that compared with people without atherosclerosis, the patients with atherosclerosis (Table 1) showed some differences in the gut microbiota (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)53). Garshick et al donated aortas of Apoe-/-mice with atherosclerosis into normolipidemic wild-type mice, then feeding antibiotic.…”
Section: Microbiota and Atherosclerosismentioning
confidence: 99%
“…Ji et al once found that Acidaminococcus was more abundant in the CAS patient. Acidaminococcus was once often enriched in patients with several inflammatory diseases and positively correlated with a proinflammatory diet, which may indicate that Acidaminococcus was a proinflammatory microbiota and represent inflammatory status in the development of AS ( 18 ). In atherosclerotic plaques, phylum Proteobacteria dominated and the phylum Firmicutes , predominantly found in the gut, is also present in atherosclerotic plaques.…”
Section: Microbiotamentioning
confidence: 99%
See 1 more Smart Citation